2018
DOI: 10.1016/j.ynstr.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for altered brain reactivity to norepinephrine in Veterans with a history of traumatic stress

Abstract: BackgroundIncreases in the quantity or impact of noradrenergic signaling have been implicated in the pathophysiology of posttraumatic stress disorder (PTSD). This increased signaling may result from increased norepinephrine (NE) release, from altered brain responses to NE, or from a combination of both factors. Here, we tested the hypothesis that Veterans reporting a history of trauma exposure would show an increased association between brain NE and mental health symptoms commonly observed after trauma, as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The increased noradrenergic tone in PTSD arises from increased central and peripheral sympathetic activity leading to increased resting heart rates and systolic blood pressure [ 47 ]. In addition, noradrenaline levels are higher in the urine of individuals with PTSD than in healthy individuals, but recent studies have failed to establish such findings in the cerebrospinal fluid (CSF) [ 48 , 49 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The increased noradrenergic tone in PTSD arises from increased central and peripheral sympathetic activity leading to increased resting heart rates and systolic blood pressure [ 47 ]. In addition, noradrenaline levels are higher in the urine of individuals with PTSD than in healthy individuals, but recent studies have failed to establish such findings in the cerebrospinal fluid (CSF) [ 48 , 49 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Evidence indicated that dysregulation of the HPA-axis resulted in low cortisol level in the blood eventually developing an inflammatory state [89]. It is noted that cortisol is glucocorticoid and is an anti-inflammatory and immunosuppressive agent [90]. Glucocorticoid further autoregulates its level via negative feedback mechanism by binding to glucocorticoid receptors in the hypothalamus and pituitary.…”
Section: Inflammation and Ptsdmentioning
confidence: 99%
“…Glucocorticoid further autoregulates its level via negative feedback mechanism by binding to glucocorticoid receptors in the hypothalamus and pituitary. Furthermore, stress triggered the release of corticotrophin hormone (CRH) in the hypothalamus that stimulates SNS to produce catecholamines including norepinephrine, a prime cause for hyperarousal in PTSD [90]. Therefore, deregulation of the HPA-axis can influence chronic inflammation (low-grade) in PTSD.…”
Section: Inflammation and Ptsdmentioning
confidence: 99%
“…Given that previous studies link the noradrenergic system to the effects of chronic stress during adolescence ( Bingham et al, 2011 ; Chaby et al, 2020 ; de Lima et al, 2017 ), and, because noradrenaline plays a key role in the acute stress response and stress related disorders such as PTSD/depression/anxiety ( Brunello et al, 2002 ; Hendrickson et al, 2018 ; Tanaka et al, 2000 ), we hypothesized that CSI would impact the noradrenergic system. To this end, we tested the noradrenaline dependent pupil response ( Privitera et al, 2020 ), and measured noradrenaline release in response to an acute swim stress using ultra-high performance liquid chromatography (uHPLC).…”
Section: Introductionmentioning
confidence: 99%